Los Elementos: sopranos in Spanish Baroque performance - Westhoven, Katherine Elise (Kansas State University, 2022)
Los Elementos (1704-1705) is a musical work that blurs the lines between Spanish and Italian Baroque performance. Written by Antonio Literes, Los Elementos is an excellent work for upper-level musicians new to early Spanish music. The piece uses predominately female roles, a feature of early Spanish music. This paper seeks to make Los Elementos more accessible to soprano performers, both to understand the roles as they fit into the larger work, as well as to provide historical and cultural context for how Los Elementos was performed, is performed, and can be performed.
Keywords: Elementos; Literes; Soprano; Baroque; Spanish